Correlation between team and co-worker relationship and employee engagement - Makera, A. U.; Nasidi, Yusuf; Kamaruddeen, A. M.; Jemaku, I. M. (Akademia Baru, 2019)
The objective of this study was to examine the correlation between team and coworker relationship and employee engagement in Federal University of Technology, Nigeria. Social exchange theory (SET) was utilized in developing the research framework. A total of 150 non-academics staff from Federal University of Technology, representing a response rate of 63.3% participated in this study. Data were collected through self-administered questionnaire. one hypothesis was tested using SPSS 2.0. The findings indicated that the relationship between team and co-worker relationship and employee engagement is low (r = .252). Theoretical and practical implications of the study as well as suggestions for future research were discussed.